Data-Driven Decision Making terkait Penetapan UKT di UIN Sunan Gunung Djati Bandung - Fauzan Hanif Abdillah; Ranti Febrianti; Jaliludin Muslim (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This paper discusses and interprets the results of several studies related to data-based decision-making. Data-based decision-making capabilities consist of Data Governance Capability, Data Analytics Capability, Performance Management Capability, Insight Exploitation Capability, and Integration Capability. The discussion is carried out by analyzing the description of four data-based decision-making capabilities related to tuition at UIN SGD Bandung: Data Governance Capability, Data Analytics Capability, Performance Management Capability, and Insight Exploitation Capability. The approach used in this study is qualitative with a case study design. The informants were obtained through a purposive sampling technique which was then tested for the validity of the results of the interviews by triangulating the data. The goal to be achieved is to describe how the process of using data in decision-making is carried out by campus authorities regarding tuition at UIN SGD Bandung so that it can produce a policy output. The findings in this study are that determining the amount of tuition accepted by UIN SGD Bandung students has gone through various processes, including using data as a reference for decision-making. However, a capability still needs to be fully fulfilled, namely, Performance Management Capability.Keywords: big data, data driven. Decision-making, tuition